INDONESIA'S FOREIGN POLICY CHANGE TOWARDS ROHINGYA ETHNIC ASYLUM SEEKERS IN 2015: A Foreign Policy Change Perspective - Grace Lumban Gaol; Prihandono Wibowo (Journal Publicuho, 2024)
In 2015, Indonesia was shocked by the landing of a foreign ship containing Rohingya refugees in Aceh province. Not only Indonesia, Malaysia and Thailand also experienced the same incident. The refugees came to obtain temporary asylum due to the country's conflict, which threatened the survival of the Rohingya tribe in Myanmar. Indonesia's rejection gave rise to various reactions from within and outside the country. Responding to this, Indonesia finally accepted the existence of Rohingya refugees by also signing the Joint Statement Ministerial Meeting on Irregular Movement of People in Southeast Asia. These foreign policy changes will be examined further using the Foreign Policy Change theory to determine the factors influencing foreign policy-makers in deciding their foreign policy. This research will use explanatory-qualitative methods to analyze Indonesia's momentum in taking windows of opportunity toward the Joint Statement Ministerial Meeting on Irregular Movement of People in Southeast Asia.